Analisis Strategi Pengembangan Kemandirian Ekonomi Pesantren dalam Menunjang Ekosistem Halal di Kabupaten Bangkalan : (Studi pada Pondok Pesantren Al Falah Kepang) - Ananda Ayu Dwi Safitri; Hammam Hammam (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Pesantren as a traditional Islamic educational institution has a significant role in the life of Indonesian society, especially in areas where the majority of the population is Muslim, such as in Bangkalan Regency, Madura. Because over time, apart from being an educational institution, pesantren also have an important role in the social and religious life of the community, not only focusing on religious education, but also starting to play a role in the economic sector, especially in developing the economic independence of pesantren which is expected to support the halal ecosystem. The main objective of this study is to find out the strategies of pesantren in increasing economic independence as well as its impact on the halal ecosystem. This study also provides recommendations regarding the development of collaboration with various parties to optimize the potential of the halal ecosystem in Madura. In this study, researchers used a descriptive qualitative approach. Researchers will examine in depth the Al Falah Kepang Islamic Boarding School in Bangkalan Regency which is active in developing an independent economy. Data will be collected through in-depth interviews, observation, and documentation. This approach was chosen to comprehensively explore the strategies implemented by pesantren that influence the development of the halal ecosystem.